Теоретико-методологические основы изучения современного (рецентного) почвообразования - Ергина, Е.И. (Культура народов Причерноморья, 2014)
В работе обосновано применение нового методологического подхода к изучению молодых
почв, находящихся в стадии формирования. Доказано, что современный процесс почвообразования
имеет специфические условия, вызванные целым рядом природных и антропогенных факторов.
Представлены математические модели формирования гумусового горизонта почв во времени У роботі обґрунтовано застосування нового методологічного підходу до вивчення молодих
ґрунтів, що перебувають у стадії формування. Доведено, що сучасний процес ґрунтоутворення має
специфічні умови, викликані цілим рядом природних і антропогенних факторів. Представлені
математичні моделі формування гумусового горизонту ґрунтів у часі Modern full height of the soil is a complex polygenetic system that reflects the diversity of the factors
of soil formation during the Holocene. The relative stability of the last phase of the Holocene allows us to say,
on the one hand, on the mapping of the properties of this period in the development of soils and landscapes. But,
on the other hand, the current state of the geographical environment , characterized by significant variability in
the first place , the climate system, the transformation of geochemical flows, activity of degradation processes,
leads to the fact that to date, the study of the evolution and development of the soil must be taken into account
the fact that the process of soil formation in the current environment occurs under conditions different from the
factors of soil formation in the early Holocene. Accordingly, the soil, which are formed in the present conditions,
will inevitably reflect a totally different features of the environment. This is true for soil, which for some reason
(anthropogenic influence or manifestation of catastrophic events), ceased to function as a system and in modern
conditions have moved to a new level of development or formation. This system will reflect the new realities of
the functioning of the geographical envelope and this suggests that the current process of soil formation is
radically different from the soil-forming process, which resulted in the modern soil.
The paper theoretically justified application of a new approach to the study of soils formed. It is shown that the
current process has specific soil conditions caused by a variety of natural and anthropogenic factors. Presented
mathematical model for the formation of soil humus horizon in time